2018
DOI: 10.1186/s13048-018-0450-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-classical 11β-hydroxylase deficiency caused by compound heterozygous mutations: a case study and literature review

Abstract: Background11β-hydroxylase deficiency (11OHD) is extremely rare, and reports of non-classical 11OHD are even rarer. Non-classical 11OHD usually presents as premature adrenarche, hyperandrogenism, menstrual disorders, and hypertension. Because the symptoms of non-classical 11OHD are mild, delayed diagnosis or misdiagnosis as polycystic ovary syndrome or primary hypertension is common.Case presentationThis paper introduces a case of a young female patient presenting hypertension and menstrual disorders. Laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…11β-OHD is the second major subtype of CAH, accounting for 0.2–8% of all CAH cases while 21-hydroxysteroid deficiency is the most common subtype of CAH ( 39 , 40 ). Mutation in CYP11B1 , encoding steroid 11β-hydroxylase (11β-OH), results in a series of pathophysiological changes, and the mutation has a significant racial specificity ( 41 ). Deficiency of 11β-OH leads to impaired conversion of 11-deoxycortisol and 11-deoxycorticosterone to cortisol and corticosterone, respectively, resulting in an elevated ACTH level and superfluous adrenal androgens.…”
Section: Genetics Of Monogenic Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…11β-OHD is the second major subtype of CAH, accounting for 0.2–8% of all CAH cases while 21-hydroxysteroid deficiency is the most common subtype of CAH ( 39 , 40 ). Mutation in CYP11B1 , encoding steroid 11β-hydroxylase (11β-OH), results in a series of pathophysiological changes, and the mutation has a significant racial specificity ( 41 ). Deficiency of 11β-OH leads to impaired conversion of 11-deoxycortisol and 11-deoxycorticosterone to cortisol and corticosterone, respectively, resulting in an elevated ACTH level and superfluous adrenal androgens.…”
Section: Genetics Of Monogenic Hypertensionmentioning
confidence: 99%
“…Firstly, some mutations which result in partial activity defects of relevant enzymes are possibly responsible for some mild phenotypes, which may be misdiagnosed easily ( 38 , 85 ). For instance, patients with the mutations in exon 3 of gene CYP11B1 tend to present as a non-classic phenotype, similar to polycystic ovary syndrome ( 41 ). Second, the overlap of germline and somatic mutations may be one of the causes of phenotypic variability.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…The CYP11B1 gene is located on the long arm of chromosome 8 (8q21–q22), and it is in very close proximity to the highly homologous CYP11B2 gene, which encodes for aldosterone synthase. About 130 mutations of the CYP11B1 gene have been described and are localized all over the gene, with a minor presence in exons 1 and 9 [128,129,130,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150]. Figure 5 summarizes the majority of allelic variants that have been described so far in the literature for females (62 patients) together with their influence on genital phenotype (see also Table S2).…”
Section: 11β-hydroxylase Deficiency (11-ohd)mentioning
confidence: 99%
“…A recent review [147] reported that the R448H mutation and eight other mutations (Q356X, G379V, T318M, c.53_54 insT, R454C, R448P, and R148X) are the most frequently found and account for approximately 40% of all cases. CYP11B1 mutations show significant ethnic specificity, and an updated description of their characteristics can be found in the studies of Khattab et al [146] and Wang et al [147].…”
Section: 11β-hydroxylase Deficiency (11-ohd)mentioning
confidence: 99%
See 1 more Smart Citation